Pengaruh Aplikasi Air Kelapa Tua dengan Cara dan Interval yang Berbeda terhadap Bobot Kering Bibit Kakao - Santi Rosniawaty; Mira Ariyanti; Cucu Suherman; Rija Sudirja; Syfani Fitria (Paspalum: Jurnal Ilmiah Pertanian, 2022)
In order to properly grow, cocoa seedling requires adequate nutrients. In a usual practice nutrient in the form of 2g of urea is given once every two weeks. The source of nutrition for cocoa seeds can come from organic materials such as coconut water. Coconut water contains nutrients and growth hormones. The purpose of this study was to determine whether coconut water could be used to fulfill the nutrition of cocoa seedling through different application methods and intervals expressed by plant dry weight. The experiment was conducted from October 2019 until February 2020 in Ciparanje experimental field, Universitas Padjadjaran, Jatinangor with the altitude of 760 meter above the sea level. Experimental design used was randomized block design (RBD) with nine treatments and each treatment was repeated three times. The treatments consisted of control (urea 2 g every 12 days), coconut water application towards plant every 3, 7, 14, 21 days, and to the soil every 3, 7, 14, 21 days. The results of the experiment showed that there was no effect of coconut water application in different methods and intervals on shoot dry weight, root dry weight, shoot root ratio and leaf area of cocoa seedling, therefore coconut water can be used as an alternative source of nutrition for cocoa seedlings.